Calcification of the external carotid arteries and their branches - MacDonald, D S (The British Institute of Radiology., 2012)
This patient had longstanding hypercalcaemia and hyperphosphataemia owing to chronic renal disease, then finally failure, inducing tertiary hyperparathyroidism. He also had long histories of diabetes mellitus type II, hypertension and hypercholesterolaemia. He then reported a painful expansile swelling of the anterior mandible which was diagnosed as a “brown tumour”. Subsequent review of the CT data set by an oral and maxillofacial radiologist revealed two patterns of calcification of the carotid arteries. A pipestem pattern was observed bilaterally along almost the entire lengths of the external carotid artery, a muscular artery, and its branches whereas plaque-like calcification was observed in the common and internal carotid arteries (elastic arteries). The pipestem pattern, hitherto an unreported feature affecting the external carotid artery, may represent a metastatic calcified deposit owing to hypercalcaemia and hyperphosphataemia in the tunica media of muscular arteries, resulting in arteriosclerosis, which maintains a patent lumen. The plaque-like pattern is representative of lumen-occluding calcified atherosclerosis associated with the long histories of diabetes mellitus type II, hypertension and hypercholesterolaemia. As this patient did not have any symptoms and/or signs of myofacial pain, facial dysfunction or numbness, the calcification of his external carotid arteries and branches were considered as arteriosclerosis. The brown tumour responded to the parathyroidectomy and the renal transplant.